Problematics of the Execution of Religious Court Decisions - Inna Fauziatal Ngazizah; Abdurrohman Kasdi; Kudrat Abdilah; Najichah Najichah; Norhasnira Ibrahim (Fiat Justisia: Jurnal Ilmu Hukum, 2025)
This article examines the problem of authority in the execution of Religious Court decisions in Indonesia and its impact on the effectiveness of Islamic law. Although Religious Courts are authorized to adjudicate family and sharia economic cases, enforcement still relies on District Courts, creating dissonance between legal norms and practice. Using a juridical-sociological qualitative approach with literature studies and interviews with two judges, one clerk, and two execution applicants, the study identifies three root problems: the absence of direct execution authority, weak cross-agency coordination, and the lack of standard operational procedures. These weaknesses disproportionately affect women and children, leaving many rulings unenforced. The article recommends regulatory reform and institutional strengthening of Religious Courts, drawing comparative insights from Malaysia and Pakistan, where religious courts have clearer enforcement mechanisms.